Desfragmentar os Espaços Perdidos da Cidade - Um Modelo de Percepção Colectiva - Guilherme Seixas de Sá Burmester (2013)
This paper attempts to understand the process of fragmentation in the contemporary city, understood both in the material (organic) and immaterial (perception) dimension, proposing an interactive and universal "map-project" of urban analysis, designed to operate collectively in the virtual network. In a first phase we seek to reflect upon the acceptance of the fragment as a structural part of the territory and as the unconscious way of working of the mind, becoming aware of the new topological dimension of urban space, characterized by the dissemination of infrastructural networks and the democratization of information technologies. This means that new trends are beginning not only to overcome the reversals of code of the modern city, but facing urban segmentation and discontinuity with a fresh perspective. In a second phase, we proceed to the construction of the method step-by-step, adopting the organizational and defragmenting process of a computer hard drive as a starting point for creating a common language, in order to optimize city space in a simple and intuitive way. It is not intended to claim that a disk proceeds and organizes in the same way as the infrastructures and constructed forms (despite of being highlighted points of contact), but to build, based on this "image", ordinary to most people, a general consciousness and unleash (re) actions about a strongly ambiguous and complex phenomenon, showing (or looking to recognize) what will be an urban enclave, through three interconnected moments (composition - discussion - decomposition) in constant development. Finally, we present a test of the final project, a look at the evolution of the city of Porto in the last ten years, synthesizing an open idea, possible to materialize in the future.